PENGARUH PROFITABILITAS, LIKUIDITAS, KEPEMILIKAN INSTITUSIONAL, LEVERAGE KEUANGAN, DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN PADA BADAN USAHA MILIK NEGARA (BUMN) YANG TERCATAT DI BURSA EFEK INDONESIA (BEI) - Nazila Rahmah; Nurhalis Nurhalis (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
This study aims to determine the effect of profitability, liquidity, institutional ownership, financial leverage, and company size on dividend policy in state-owned enterprises (BUMN) listed on the Indonesia Stock Exchange (IDX). This study uses panel data with 20 state-owned companies listed on the Indonesia Stock Exchange (IDX) from the 2016-2020 period. The analytical method used is panel data regression analysis using Eviews 10. The sampling technique used is purposive sampling with multiple linear regression data analysis fixed effect model. The results of this study partially show that profitability and liquidity have a positive and significant effect on dividend policy, institutional ownership and financial leverage have a negative and significant effect on dividend policy, and firm size has a negative and not significant to dividend policy in State-Owned Enterprises (BUMN).